Aspek Yuridis Penerapan Sanksi Adminisratif Bagi Pelaku Kecurangan (FRAUD) Dalam Program Jaminan Kesehatan Nasional - Andi Ashar (Pusat Riset dan Inovasi Nasional, 2022)
The National Health Insurance Program is the Government's effort to provide guarantees so that health services are provided to Participants in the National Health Insurance Program. In its implementation, there is a risk in the form of fraud committed by unscrupulous persons. The consequence of fraud is the imposition of sanctions which are an important part of every law and regulation. One of the imposition of sanctions for perpetrators of fraud is administrative sanctions. Administrative sanctions that arise do not erase criminal sanctions in accordance with the provisions of the legislation. Administrative sanctions are considered to be far more effective in forcing people to comply with legal provisions governing business and industry and environmental protection than criminal sanctions. With the imposition of these sanctions it is expected to maintain the sustainability of the National Health Insurance Program